Effect of chitosan-based coating on post-harvest quality of 'mata kucing' (Euphoria malaiense) / Fatimah Hanisah Ahmad Radzuan and Boon Yih Tien - Ahmad Radzuan, Fatimah Hanisah; Boon, Yih Tien (2021)
The coating method is one of the preservation techniques that has been widely used in preserving post-harvest fruits due to its effectiveness in maintaining the quality, increasing the shelf life, and reducing the wastage of the post-harvest fruits. The chitosan-based coating is one of the edible fruits preserving post-harvest coating as it is able to maintain the quality of fruits such as colour, texture, moisture, sugar content, as well as the flavour of the fruits. This review aims to give an overview of the different treatments of the chitosan-based coating method on 'mata kucing'. The processing and preservation of the 'mata kucing' are recommended to be carried out after their harvest using cinnamaldehyde-chitosan and 2% chitosan treated with glacial acetic acids. The pH should be adjusted from pH 5.0 to 5.5 to avoid precipitation and to provide a good coating solution. The chitosan-based coating is generally safe for human health however it is not recommended for those who are allergic to shellfish. Thus, future research is needed to ensure the safety of chitosan-based coating products especially for those who are allergic to shellfish.